Radiolabeled Liposomes for Nuclear Imaging Probes - Ho Ying Low; Chang-Tong Yang; Bin Xia; Tao He; Winnie Wing Chuen Lam; David Chee Eng Ng (Molecules, 2023)
Quantitative nuclear imaging techniques are in high demand for various disease diagnostics and cancer theranostics. The non-invasive imaging modality requires radiotracing through the radioactive decay emission of the radionuclide. Current preclinical and clinical radiotracers, so-called nuclear imaging probes, are radioisotope-labeled small molecules. Liposomal radiotracers have been rapidly developing as novel nuclear imaging probes. The physicochemical properties and structural characteristics of liposomes have been elucidated to address their long circulation and stability as radiopharmaceuticals. Various radiolabeling methods for synthesizing radionuclides onto liposomes and synthesis strategies have been summarized to render them biocompatible and enable specific targeting. Through a variety of radionuclide labeling methods, radiolabeled liposomes for use as nuclear imaging probes can be obtained for in vivo biodistribution and specific targeting studies. The advantages of radiolabeled liposomes including their use as potential clinical nuclear imaging probes have been highlighted. This review is a comprehensive overview of all recently published liposomal SPECT and PET imaging probes.